Reliability Level Evaluation of Passive Fire Protection System in Hospital Buildings (Case Study: Grandmed Lubuk Pakam Hospital) - Novrial; WH Novi (International Journal of Architecture and Urbanism, 2019)
This research focuses only on passive fire protection systems in-hospital buildings because the Hospital is public buildings that many people use as facilities for health needs. Hospital residents are not only healthy people, but most sick people are not able to save themselves because of that the building safety system must be reliable especially fire protection systems. This study uses descriptive analysis method by checking directly in the field against the variables that have determined and then analyzed, based on the weight of the AHP method after that each variable and sub-variable will be assessed with a Likert scale according to its suitability with regulations and standards, then weights will be multiplied by the value of conformity to get the reliability value. The results are the level of reliability of the building fire passive protection system 2,250 it includes which in the category enough. This is to increase the value of the level of reliability, it must fulfill the design guidelines in the form of standards.